(untitled) (Shahroud Journal of Medical Sciences, 2017)
Background: Cardiovascular disease is one of the main causes of mortality in the world and is primarily caused by high blood lipids. This study aimed to compare the effect of garlic and lemon mixture with mucilage of the okra pods in preventing the increase of plasma lipids in male Ratus.Methods: This study was performed on 34 Ratus norvegicus alluvia. The Ratus were randomly divided into two classes, which were further subdivided in three groups each. A class of Ratus received food mixed with market oils for 60 days. Moreover, the Ratus in the treatment group received 10% okra mucilage and the mixture of garlic and lemon as gavage for 3 weeks. Data were analyzed by SPSS-21 software. The Mann–Whitney nonparametric test was used to compare each pair of groups. A value of 5% was considered as statistically significant.Results: Comparing the control group and the group receiving oil, we observed that lipid intake was effective and significantly increased the blood cholesterol in the oil group (p = 0.006). In Ratus receiving fatty foods, it was observed that treatment regimens reduced blood lipids. Moreover, a significant difference was observed between the two treatment groups, indicating a 10% mucilage advantage in reducing blood lipids compared with other treatment groups.Conclusions: The results indicate that both treatments reduce blood lipids, but 10% mucilage in Ratus with high blood lipids has better efficacy than garlic and lemon mixture in reducing blood lipids.